Proyecto de factibilidad para la implementación de un semanario comunitario en el cantón Nangaritza, provincia de Zamora Chinchipe”, periodo mayo-diciembre de 2010 - Lojano, Raúl Javier (2014)
This research work is part of a study of the in habitants of the canton Nangaritza on "the feasibility of implementing a weekly community" whose purpo se is to streng then the communication process ses bet ween its inhabitants and development institutions. Among the key findings was determined that its inhabitants do not buy the newspaper, due to the lack of a rotating within the locality, so that the need for a community weekly was confirmed. The investigation was based on the scientific method: Inductive, Statistical and Analytical-Synthetic, including the inhabitants of the study area, in order to implementa community weekly that will help streng then communication process es a mong the inhabitants of the canton Nangaritza and development institutions. In the course of investigating the use of techniques such as literature, observation and survey data collection allowed the information to make a diagnos is about there search where the absence of an information paper is eviden cebe cam e indispensable. As a result of there search the o retical frame work related to the topic of study was develop dallowing creating project feasibility for the implementation of a community weekly news paperin the canton Nangaritza.